Nitrogen Retention Value in Local Sheep Fed with Dwarf Elephant Grass (Pennisetum purpureum cv. Mott) and Indigofera (Indigofera zollingeriana) - Nuswantara, Limbang Kustiawan; Firmansyah, Afandy; Christiyanto, Marry (Jurnal Agripet, 2025)
This study aimed to determine the nitrogen retention in local sheep fed dwarf elephant grass (Pennisetum purpureum cv. Mott) and indigofera (Indigofera zollingeriana). A completely randomized design (CRD) was used, consisting of four treatments with four replications each. The dietary treatments included: T= 100% dwarf elephant grass, T= 95% dwarf elephant grass + 5% indigofera, T2= 90% dwarf elephant grass + 10% indigofera, and T= 85% dwarf elephant grass + 15% indigofera. The parameters measured were dry matter intake (DMI), dry matter digestibility (DMD), nitrogen (N) intake, N retention, and average daily gain (ADG). The results showed that DMI, DMD, N intake, N retention, and ADG were significantly (P0.05) influenced by the dietary treatments. Based on these findings, the combination of 95% dwarf elephant grass and 5% indigofera was the most effective in improving DMI, DMD, N intake, N retention, and ADG in local sheep.